2018
DOI: 10.1016/j.nutres.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intervention with an Okinawan-based Nordic diet in type 2 diabetes renders decreased interleukin-18 concentrations and increased neurofilament light concentrations in plasma

Abstract: Diabetes mellitus is characterized by low-grade inflammation and cognitive impairment. An Okinawan-based Nordic (O-BN) diet rendered improved anthropometry and metabolism. The aim of this study was to examine the inflammatory and neural responses after O-BN diet in health and type 2 diabetes (T2D). Two different breakfasts; one standard and one O-BNbased, were given in random order to 19 healthy volunteers. A 12-week O-BN-dietary intervention in T2D was performed, and the participants were followed for another… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 52 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…Since this was a pilot-study investigating the effects of the SSRD on IBS patients, no power analysis was performed due to lack of previous data. However, our research team has previously investigated the effect of a carbohydrate-reduced diet on type 2-diabetes patients, where 23 participants demonstrated improved GI symptoms and changes in systemic cytokine expression after 12 weeks [30,31]. As the dietary intervention in the present study was of a shorter duration, we hypothesized that more participants would be required to show a possible effect of the SSRD.…”
Section: Study Group Sizementioning
confidence: 98%
“…Since this was a pilot-study investigating the effects of the SSRD on IBS patients, no power analysis was performed due to lack of previous data. However, our research team has previously investigated the effect of a carbohydrate-reduced diet on type 2-diabetes patients, where 23 participants demonstrated improved GI symptoms and changes in systemic cytokine expression after 12 weeks [30,31]. As the dietary intervention in the present study was of a shorter duration, we hypothesized that more participants would be required to show a possible effect of the SSRD.…”
Section: Study Group Sizementioning
confidence: 98%
“…The link between DII and T2DM can be explained by the effect of a pro-inflammatory diet on insulin resistance, which is associated with the inflammatory state (Roden & Shulman, 2019). Previous studies have shown that systemic, chronic low-grade inflammation characterized by continuous elevation of inflammatory factors in the circulatory system is associated with the occurrence and development of T2DM (Gardener, Rainey-Smith & Martins, 2016;Nilholm et al, 2018). Inflammatory factors such as IL-6 (Fadaei et al, 2020), TNF-α, and CRP have been shown to predict the risk of T2DM (Akour et al, 2018); however, the specific mechanism remains unclear (Naidoo, Naidoo & Ghai, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that a high intake of fruits and vegetables have positive effects on inflammation. [15,35,36] Diets with a naturally high content of fibers and phytochemicals from fruits, vegetables, berries, nuts, and plant-oils (such as Mediterranean diet, [9,[37][38][39][40][41][42][43] Nordic diet, [44,45] or disease prevention diets like DASH [46][47][48] ), have been investigated for their health benefits. Overnutrition and physical inactivity mediate an increased leakage of LPS from the intestine, an increased mass of adipose tissue resulting in an induced state of inflammation (cytokines) and ROS production.…”
Section: Effects Of Dietsmentioning
confidence: 99%
“…Many studies have shown that a high intake of fruits and vegetables have positive effects on inflammation. [ 15,35,36 ] Diets with a naturally high content of fibers and phytochemicals from fruits, vegetables, berries, nuts, and plant‐oils (such as Mediterranean diet, [ 9,37–43 ] Nordic diet, [ 44,45 ] or disease prevention diets like DASH [ 46–48 ] ), have been investigated for their health benefits. The DASH and new Nordic diets are known for their lower content of saturated fatty acids, mainly due to restriction for low‐fat dairy compared to the MedDiet.…”
Section: Introductionmentioning
confidence: 99%